The correlation abortion history with LBWI - Ika Septiana Cahyaningtyas; Endah Marianingsih Theresia; Wafi Nur Muslihatun (Jurnal Kesehatan Ibu dan Anak, 2018)
Low Birth Weight Infant (LBWI) are one of the causes of infant mortality. LBWI is a condition where babies born with a body weight less than 2500 grams.The prevalence of LBWI in Special Region of Yogyakarta or DIY in the last three years has fluctuated. Kulon Progo Regency is one of the districts in DIY with the highest prevalence of LBWI and there was also an increase from previous year. One of the risk factors LBWI is abortionhistory. This study was to know the correlation between abortion history with LBWI in Wates General Hospital in 2017. This study was an analytic observational study with cross sectional design. The sampling technique was purposive sampling.Samples in this study were 177 subjects who had inclusion and exclusion criteria.The data analysis used chi square. The result of this study showed that LBWI in mothers with a history of abortion (38.6%) was greater than LBWI in mothers with no history of abortion (21.8%). Based on chi square test known p value = 0,045 with prevalence ratio 1.809 (CI 95% 1,085-4,701). There was a correlation between abortion history with LBWI in Wates General Hospital in 2017.